The Role of Smart Actuarial Calculations in Improving the Quality of Financial Reports of the Iraqi Insurance Company - Allayla, Zena Abdulstar; Al-Ibrahimi, Waheed Mahmood (Journal of Economics and Administrative Sciences, 2025)
The research aims to explore the role of actuarial calculations supported by artificial intelligence technologies (smart actuarial calculations) in enhancing the accuracy and quality of financial reporting. Companies face challenges related to the accuracy, transparency, and speed of preparing financial reports, necessitating innovative solutions based on smart technologies. The research analyzed the literature and employed an exploratory methodology to study the impact of smart actuarial calculations on the integrity of financial reports. The association between the application of artificial intelligence and professional standards and their impact on the performance of insurance companies and financial reporting practices was also examined. The researchers concluded that smart actuarial calculations enhance the quality of financial reports by increasing accuracy and speed, providing comprehensive analyses, reducing costs, and increasing efficiency through the reduction of human errors and precise risk analysis. These calculations also enhance compliance with accounting standards, build shareholder and stakeholder confidence, and emphasize the importance of professional standards and actuarial guidelines to ensure the quality of work. The research recommended improving the utilization of artificial intelligence in developing actuarial calculations, providing continuous training for experts, adhering to professional standards to ensure transparency and reliability, and encouraging future studies to investigate the implications of smart technology in the accounting and insurance fields. This research contributes to accounting literature by providing insights into artificial intelligence’s role in developing actuarial calculations and improving insurance sector performance.